Pemanfaatan Limbah Cangkang Kerang sebagai Subtitusi Agregat Kasar dengan Bahan Tambah Superplasticizer terhadap Kuat Tekan - Muhammad Ilham Tahir; Jasman Jasman; Misbahuddin Misbahuddin; Adnan Adnan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Parepare City is located on the coast with significant fisheries and maritime potential. The processing and consumption of shellfish in this city produces a lot of shellfish waste, which is often not utilized and accumulates into an environmental problem. To improve the properties of concrete, several types of additives that have certain functions are added to the concrete mixture, namely increasing the workability, durability, and hardening time of concrete. This study aims to determine the compressive strength of concrete and the composition of coarse aggregate of shells with superplasticizer added materials that are optimally produced. Using an experimental method carried out at the Laboratory of Structure and Materials, Muhammadiyah University of Parepare. The results showed that substitution of coarse aggregate with 5% shellfish waste and 0.5% superplasticizer increased the compressive strength of concrete at the ages of 7, 14, and 28 days. The 10% substitution still meets the compressive strength requirements at 28 days, although slightly lower than normal concrete. Substitution of shells up to 5% increases the compressive strength of concrete, and the 10% content is optimal, reaching the maximum value without significant decline. It is recommended that the use of shells as a substitute for coarse aggregate does not exceed 10% for optimal results and meets the planned compressive strength of 25 MPa.